Downregulated ribosomal protein L39 inhibits trophoblast cell migration and invasion by targeting E‐cadherin in the placenta of patients with preeclampsia. Issue 4 (12th March 2021) - Jie, Qiuling; Sun, Fei; Li, Qi; Zhu, Juan; Wei, Yunjian; Yang, Huamei; Long, Ping; Wang, Zhen; Yang, Xiaohui; Li, Dan; Huang, Liping; Ma, Yanlin
Abstract: Early‐onset preeclampsia (PE) is a pregnancy complication that can lead to severe adverse maternal and fetal outcomes. However, the mechanisms underlying the development of early‐onset PE are not fully understood. Ribosomal protein L39 (RPL39) is a member of the S39E family of ribosomal proteins that plays an important role in stem cell self‐renewal, cancer metastasis, and chemoresistance. In this study, we aimed to explore the potential function of RPL39 in placental trophoblast cells. We analyzed the expression of RPL39 in early‐onset PE and normal placental tissues using real‐time PCR, western blot analysis, and immunohistochemistry. The results showed that RPL39 was markedly downregulated in early‐onset PE placental tissues. RPL39 knockdown inhibited trophoblast cell proliferation, migration, and invasion, as well as placental explant outgrowth. Flow cytometry analysis suggested that knockdown of RPL39 resulted in cell cycle arrest at the G0/G1 phase, but had no significant effect on cell apoptosis. We also found that RPL39 knockdown could alter cell morphology. We then measured the expression of the epithelial cell marker E‐cadherin following knockdown of RPL39 in Bewo and HTR8/SVneo cells. RPL39 knockdown increased the expression of E‐cadherin. Furthermore, E‐cadherin expression was upregulated in placental explant outgrowth tissues transfected with RPL39 small interfering RNA. In conclusion, RPL39 plays an essential role in proliferation, invasion, and migration of trophoblast cells by targeting E‐cadherin. Our findings provide novel insight into the mechanisms underlying the occurrence of early‐onset PE.